Anti-fading dyed fabric and production method thereof
By using ingredients such as onion extract, eucalyptus leaf extract and other ingredients to prepare dye liquid, combined with ultrasonic treatment and temperature-controlled soaking technology, the problem of easy fading of existing dyed fabrics is solved, and fabric production with high color fastness, antibacteriality and breathability is achieved.
Patent Information
- Application Number
- CN202411746203.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-07
AI Technical Summary
Existing dyed fabrics are prone to fading during use and washing, and the combination of color materials and fibers is relatively weak, resulting in poor light resistance, washing resistance, friction resistance and other properties.
The dye solution is prepared by onion extract, eucalyptus leaf extract, acacia-echinacea complex, soapy soil complex and insect secretions. Through ultrasonic treatment and temperature-controlled soaking and other processes, the fixity and color fastness of color material molecules are improved.
It significantly improves the anti-fading ability, antibacterial properties and breathability of the fabric, extends the service life of the product, and reduces production costs.
Smart Images

Figure BDA0005163790280000071 
Figure BDA0005163790280000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of clothing fabric preparation, and in particular relates to a fade-resistant dyed fabric and a production method thereof. Background Art
[0002] Dyed fabrics refer to fabrics that are processed through a series of processes using professional dyeing equipment to give them various colors. Dyed fabrics are widely used in clothing, home furnishings, industry and other fields. Anti-fading dyed fabrics are fabrics that have been specially treated to reduce or prevent fading during use and washing. The anti-fading property of dyed fabrics is one of the important indicators for evaluating their quality. This kind of fabric can maintain its bright color. Even after multiple washings and long-term use, it is not easy to fade significantly, so that clothing, household items, etc. always maintain a good appearance. Due to its anti-fading properties, the fabric is usually more durable and can withstand the influence of daily wear, friction and light, extending the service life of the product.
[0003] In order to make the fabric have higher color fastness, the fiber is generally dyed first, and then the fiber is woven into fabric. The existing fiber dyeing production cycle is long, and the fiber dyeing needs to go through multiple processes, including pre-treatment, dyeing, post-treatment, etc. The whole process is relatively complicated and time-consuming, and the dyed fiber needs to be dried, stored, etc., which increases the production cycle. Compared with the method of dyeing the fiber first and then weaving it into fabric, the method of weaving it into fabric first and then dyeing it has high production flexibility, and the color and pattern of the fabric can be adjusted at any time according to market demand. There is no need to prepare a large number of fibers of different colors in advance. Fabric dyeing can adopt a relatively simple dyeing process and equipment, and the cost is relatively low. However, the existing dyeing solution is relatively weak in combination with the fiber, and the light resistance, washing resistance, friction resistance and other properties are not ideal. In the subsequent use and washing process, fading is easy to occur. If the anti-fading ability is to be improved, the amount of dyeing solution needs to be increased. Excessive use of dyeing solution will increase the production cost on the one hand, and on the other hand, it is easy to reduce other properties of the fabric, such as air permeability and softness.
[0004] To this end, we provide a fade-resistant dyed fabric and a production method thereof to solve the above-mentioned problems. Summary of the invention
[0005] The purpose of the present invention is to provide a fade-resistant dyed fabric and a production method thereof in view of the problems of the background technology.
[0006] The present invention achieves the above-mentioned purpose through the following technical solutions:
[0007] A fade-resistant dyed fabric, wherein raw materials for preparing the fabric include grey cloth and a dye solution for coloring the grey cloth, wherein the raw materials for preparing the dye solution include, by weight, 5-8 parts of onion extract, 10-12 parts of eucalyptus leaf extract, 5-8 parts of a saponin-echinacea complex, 1-2 parts of a bentonite complex, 3-5 parts of insect secretions, 5-7 parts of a colorant and 100-120 parts of deionized water; the saponin-echinacea complex is obtained by treating a saponin extract and an echinacea extract with citric acid; and the bentonite complex is obtained by treating bentonite and lignin with oxalic acid.
[0008] As a further optimization scheme of the present invention, the mass ratio of the saponin extract, the echinacea extract and the citric acid is 1:0.3-0.5:0.06-0.10.
[0009] As a further optimization scheme of the present invention, the preparation steps of the saponin-echinacea complex are: respectively dispersing the saponin extract and the echinacea extract in 10-12 times the mass of ethanol to obtain the saponin extract and the echinacea extract, mixing the saponin extract and the echinacea extract evenly, then slowly adding citric acid, applying ultrasound with a frequency of 25-30KHz and a time of 20-30min to the dispersion after mixing evenly, then controlling the temperature of the dispersion to 50-60°C, the pH to 5-6, the reaction time to 3-4h, and after the reaction is completed, using ultrafiltration equipment for separation and purification, and drying to obtain a powdered saponin-echinacea complex.
[0010] As a further optimization scheme of the present invention, the mass ratio of bentonite, lignin and oxalic acid is 1:0.5-0.6:0.1-0.2.
[0011] As a further optimization scheme of the present invention, the preparation steps of the bentonite composite are: dispersing powdered lignin in 6-8 times the mass of deionized water to obtain a lignin dispersion, then slowly adding bentonite to the lignin dispersion, mixing evenly, and then slowly adding oxalic acid, after mixing evenly, applying ultrasound with a frequency of 15-20KHz and a time of 15-20min to the dispersion, letting the mixture stand for 30-40min, and filtering to obtain a liquid bentonite composite.
[0012] As a further optimization scheme of the present invention, the insect secretion is the lacquer liquid secreted by lacquer insects.
[0013] As a further optimization scheme of the present invention, the onion extract is obtained by crushing onions, soaking them in ethanol, and then filtering, concentrating, and spray-drying the extract; the eucalyptus leaf extract is obtained by crushing eucalyptus leaves, soaking them in ethanol, and then filtering, concentrating, and spray-drying the extract; the soapberry extract is obtained by crushing mature soapberries, soaking them in ethanol, and then filtering, concentrating, and spray-drying the extract; the echinacea extract is obtained by crushing mature echinacea whole plants, soaking them in ethanol, and then filtering, concentrating, and spray-drying the extract.
[0014] As a further optimization solution of the present invention, the grey cloth is woven from polyester fibers.
[0015] The present invention also provides a method for producing a fade-resistant dyed fabric, comprising the following steps:
[0016] S1. Dispersing the colorant in deionized water, mixing evenly, respectively adding onion extract, eucalyptus leaf extract, sapodilla-echinacea complex and bentonite complex to the dispersion, mixing evenly, then adding insect secretions to the dispersion, mixing evenly, applying ultrasound at a frequency of 30-40 KHz and a time of 30-40 min to the dispersion to obtain a dye solution;
[0017] S2. Control the temperature of the dye solution to 50-55°C, soak the grey cloth in the dye solution for 30-40 minutes, and stir continuously during the soaking period;
[0018] S3, taking out the grey cloth and performing drying and curing treatment to obtain the anti-fading dyed fabric.
[0019] The beneficial effects of the present invention are:
[0020] 1. The present invention adopts saponin extract and echinacea extract to prepare dye solution, and saponin extract and echinacea extract form a complex through citric acid, which can greatly improve the fixation and color fastness of colorant molecules, have better permeability, can penetrate into the interior of grey cloth fibers, and provide certain antibacterial properties.
[0021] 2. The present invention uses bentonite to prepare the dye solution. Since bentonite itself has a large specific surface area and a rich pore structure, it can absorb colorant molecules, thereby improving the anti-fading ability of the fabric and improving the air permeability.
[0022] 3. The present invention uses lignin, oxalic acid and bentonite to form a bentonite composite, which improves the adsorption performance of bentonite, improves the dispersibility and stability of bentonite, further enhances the adhesion of the colorant on the grey cloth fiber, improves the color fastness of the colorant, and thus improves the anti-fading ability of the fabric. DETAILED DESCRIPTION
[0023] The present application is described in further detail below. It is necessary to point out that the following specific implementation methods are only used to further illustrate the present application and cannot be understood as limiting the scope of protection of the present application. Technicians in this field can make some non-essential improvements and adjustments to the present application based on the above application content.
[0024] 1. Main instruments and materials
[0025] The instruments used in the present invention, such as ultrasonic equipment, mechanical stirring equipment, and drying equipment, are conventional instruments known to those skilled in the art unless otherwise specified, and the reagents and other materials used are commercially available products unless otherwise specified.
[0026] The onion extract is prepared by immersing onions in 70% ethanol at 30-40°C for 24 hours after crushing, wherein the crushing particle size is 40-80 meshes, and the solid-liquid ratio is 1:15 (g / mL). The extract is then filtered to remove impurities and insolubles, and then the filtrate is placed in a rotary evaporator for distillation to remove irritating odor components, the distillation temperature is controlled at 80-85°C, and the onion is concentrated to about 10% of the total volume, and finally spray-dried to obtain the extract.
[0027] The eucalyptus leaf extract is prepared by crushing the eucalyptus leaves and soaking them in 70% ethanol at 30-40°C for 24 hours, the crushing particle size is 40-80 mesh, the solid-liquid ratio is 1:15 (g / mL), and then the extract is filtered to remove impurities and insolubles, and then the filtrate is concentrated by a concentration device (such as a concentration tank), the concentration temperature is controlled at 50-60°C, and concentrated to about 10% of the total volume, and finally spray-dried to obtain the extract.
[0028] The soapberry extract is prepared by crushing mature soapberries and then soaking them in 80% ethanol at 30-40°C for extraction for 36 hours, with a crushing particle size of 40-80 meshes and a solid-liquid ratio of 1:10 (g / mL). The extract is then filtered to remove impurities and insoluble matter, and the filtrate is then concentrated through a concentration device (such as a concentration tank) with the concentration temperature controlled at 50-60°C to about 10% of the total volume, and finally spray-dried to obtain the extract.
[0029] Echinacea extract is prepared by crushing the mature whole plant of Echinacea, soaking it in 80% ethanol at 30-40°C for 36 hours, crushing the particle size to 40-80 mesh, and the solid-liquid ratio to 1:10 (g / mL). The extract is then filtered to remove impurities and insoluble matter, and the filtrate is then concentrated by a concentration device (such as a concentration tank), the concentration temperature is controlled at 50-60°C, and concentrated to about 10% of the total volume, and finally spray-dried to obtain the extract.
[0030] 2. Implementation of the experiment
[0031] Dye solutions with different components were selected to prepare dyed fabrics, as shown in Table 1, and the dyed fabrics were prepared according to the following preparation method:
[0032] S1. Dispersing the pigment in deionized water, the specific type of the pigment is determined based on actual needs, and then adding onion extract, eucalyptus leaf extract, saponin-echinacea complex and bentonite complex to the dispersion respectively after mixing evenly, and then adding insect secretions, such as lacquer liquid secreted by lacquer insects, to the dispersion after mixing evenly, applying ultrasound at a frequency of 35 KHz and a time of 35 min to the dispersion after mixing evenly to obtain a dye solution;
[0033] The saponin-echinacea complex is obtained by treating a saponin extract and an echinacea extract in a mass ratio of 1:0.4:0.08 with citric acid. Specifically, the saponin extract and the echinacea extract are respectively dispersed in 11 times the mass of ethanol to obtain a saponin extract and an echinacea extract. The saponin extract and the echinacea extract are evenly mixed, and then citric acid is slowly added. After evenly mixing, ultrasonic waves with a frequency of 28KHz and a time of 25min are applied to the dispersion. Then, the temperature of the dispersion is controlled to 55°C, the pH is 5.5, and the reaction time is 3.5h. After the reaction is completed, ultrafiltration equipment is used for separation and purification, and the powdered saponin-echinacea complex is obtained by drying.
[0034] The bentonite composite is obtained by treating bentonite and lignin with oxalic acid in a mass ratio of 1:0.55:0.15. Specifically, powdered lignin is dispersed in 7 times the mass of deionized water to obtain a lignin dispersion, and then bentonite is slowly added to the lignin dispersion, and after mixing evenly, oxalic acid is slowly added, and after mixing evenly, ultrasonic waves with a frequency of 18KHz and a time of 18min are applied to the dispersion, and the mixture is allowed to stand for 35min, and a liquid bentonite composite is obtained after filtering;
[0035] S2. Control the temperature of the dye solution to 52°C, and soak the grey cloth made of polyester fiber in the dye solution for 35 minutes, stirring continuously during the soaking period;
[0036] S3, taking out the grey cloth and performing drying and curing treatment to obtain the anti-fading dyed fabric.
[0037] Table 1 Raw material components for dye solution preparation
[0038]
[0039] Note: “-” means no addition, ordinary saponin-echinacea complex refers to saponin extract and echinacea extract that have not been treated with citric acid complex, and ordinary bentonite complex refers to bentonite and lignin that have not been treated with oxalic acid.
[0040] Take several groups of dyed fabrics prepared with AG dye solution of the same mass and make uniform test samples with the specification of 20cm×20cm×0.5mm. Set blank sample 1, dyed fabric prepared with conventional dye solution, and blank sample 2, fabric not treated with dye solution. Perform the following tests on the samples respectively:
[0041] (1) Light fastness test:
[0042] Place the sample together with the standard color sample fabric in the testing machine and expose it under the specified conditions. After a certain period of exposure, such as 24 hours, take out the sample and compare it with the unexposed part to evaluate the degree of color change. The light fastness is divided into 8 levels. The higher the level, the better the anti-fading ability. After taking the average value of multiple groups of experiments, the test results are statistically obtained in Table 2 below.
[0043] (2) Rubbing color fastness test:
[0044] Place the sample on a friction fastness tester and rub it a certain number of times with a standard friction white cloth under a certain pressure. Then use a gray card to rate the color stained on the standard friction white cloth. The friction color fastness is divided into 5 levels. The higher the level, the better the anti-fading ability. After taking the average value of multiple groups of experiments, the test results are statistically obtained in Table 2 below.
[0045] (3) Washing color fastness test:
[0046] The samples were washed in a washing machine together with a certain amount of standard detergent under specified conditions. The color fastness to washing was evaluated according to the standard by comparing the color changes of the washed samples with those of the original samples. The color fastness to washing was divided into 5 levels. The higher the level, the better the anti-fading ability. After taking the average value of multiple groups of experiments, the test results were statistically obtained in Table 2 below.
[0047] (4) Antibacterial test:
[0048] A sample of 20cm×20cm×0.5mm was cut into multiple small pieces, such as 4cm×4cm×0.5mm. The small fabric sample was contacted with an agar medium inoculated with test bacteria (such as Staphylococcus aureus). After a period of cultivation, it was observed whether an inhibition zone was formed around the small fabric sample. The larger the inhibition zone, the better the antibacterial performance. After taking the average value of multiple groups of experiments, the test results were statistically obtained in Table 2 below.
[0049] (5) Air permeability test:
[0050] The sample is fixed in the test area of the air permeability test instrument (such as Gurley air permeability tester), the air flow rate and pressure are set according to the test requirements, the test instrument is started, and the gas flow of the sample within a specified time (such as 1 minute) is recorded. The larger the gas flow, the better the air permeability. After taking the average value of multiple groups of experiments, the test results are statistically obtained in Table 2 below.
[0051] Table 2 Test parameters of dyed fabrics
[0052]
[0053] 3. Results Analysis
[0054] 1. Combined with the above table, the comparison of the test data of fabrics A, B, C with other fabrics shows that the color fastness to sunlight, color fastness to friction and color fastness to washing of the fabrics are significantly better than those of other fabrics, indicating that fabrics A, B, C have better anti-fading ability, and the antibacterial zone diameter test data of fabrics A, B, C are also better than those of other fabrics, and the air permeability is slightly weaker than that of blank sample 2, indicating that fabrics A, B, C have enhanced their antibacterial properties while ensuring their anti-fading ability, while their air permeability has not decreased significantly, which solves the problem that the traditional method of weaving fabrics first and then dyeing them has low color fastness, and the combination of colorants and fibers is relatively weak, and fading is prone to occur during subsequent use and washing.
[0055] 2. Combined with the above table, the comparison of the test data of fabrics D, E and A shows that when preparing the dye solution, the addition of the saponin-echinacea complex can greatly improve the anti-fading ability and antibacterial property of the fabric, but its improvement on the breathability is not obvious. The saponin in the saponin extract can provide good surface activity and adhesion. The echinacea extract is rich in polyphenols and bioactive ingredients, which helps to improve the fixation and color fastness of the colorant molecules. The triterpenoid saponins in the saponin extract and the polysaccharides, caffeic acid derivatives and other active ingredients in the echinacea extract can be combined by force to form a complex. The complex has better biological activity and stability than a single extract, and is further treated with citric acid to improve the permeability and can penetrate into the interior of the grey cloth fiber. The eucalyptus leaf extract and the saponin-echinacea complex have natural antibacterial properties and can inhibit bacterial growth.
[0056] 3. Combined with the above table, the comparison of the test data of fabrics F, G and A shows that the addition of bentonite complex in the preparation of dye solution can greatly improve the anti-fading ability of the fabric and significantly improve the air permeability of the fabric. Bentonite itself has a large specific surface area and rich pore structure, which can adsorb colorant molecules, making the colorant more firmly bound to the grey fabric fiber, reducing the free state of colorant molecules in water, thereby reducing the loss of colorant molecules during washing, thereby improving the anti-fading ability of the fabric and improving the air permeability. In order to improve the performance of bentonite, bentonite and wood Lignin and oxalic acid are combined to form a bentonite complex. Lignin itself has rich functional groups and good stability. After combining with bentonite, the adsorption performance and environmental protection of the complex can be improved. The lignin functional groups can combine with the colorant molecules to enhance the adsorption of the colorant on the bentonite complex. Oxalic acid can improve the dispersibility and stability of bentonite, making it easier to disperse evenly in the solution, improve its compatibility with other substances, enhance the adsorption capacity of bentonite, further enhance the adhesion of the colorant on the grey cloth fiber, improve the color fastness of the colorant, and thus improve the anti-fading ability of the fabric.
[0057] The above-mentioned embodiment only expresses one implementation mode of the present invention, and its description is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A fade-resistant dyed fabric, the raw materials for preparation include grey cloth and dye solution for coloring the grey cloth, characterized in that: The raw materials for preparing the dye solution include, by weight, 5-8 parts of onion extract, 10-12 parts of eucalyptus leaf extract, 5-8 parts of Gleditsia-Echinacea complex, 1-2 parts of bentonite complex, 3-5 parts of insect secretions, 5-7 parts of colorant and 100-120 parts of deionized water; The Gleditsia sinensis-Echinacea complex is obtained by treating Gleditsia sinensis extract and Echinacea purpurea extract with citric acid; The bentonite composite is obtained by treating bentonite and lignin with oxalic acid.
2. The anti-fading dyed fabric according to claim 1, characterized in that: The mass ratio of the sapodilla extract, the echinacea extract and the citric acid is 1:0.3-0.5:0.06-0.
10.
3. The anti-fading dyed fabric according to claim 2, characterized in that: The preparation steps of the saponin-echinacea complex are as follows: respectively dispersing the saponin extract and the echinacea extract in 10-12 times the mass of ethanol to obtain a saponin extract and an echinacea extract, uniformly mixing the saponin extract and the echinacea extract, then slowly adding citric acid, applying ultrasound with a frequency of 25-30KHz and a time of 20-30min to the dispersion after uniform mixing, then controlling the temperature of the dispersion to 50-60°C, the pH to 5-6, the reaction time to 3-4h, and after the reaction is completed, separating and purifying by ultrafiltration equipment, and drying to obtain a powdered saponin-echinacea complex.
4. The anti-fading dyed fabric according to claim 1, characterized in that: The mass ratio of the bentonite, lignin and oxalic acid is 1:0.5-0.6:0.1-0.
2.
5. The anti-fading dyed fabric according to claim 4, characterized in that: The preparation steps of the bentonite composite are as follows: dispersing powdered lignin in 6-8 times the mass of deionized water to obtain a lignin dispersion, then slowly adding bentonite into the lignin dispersion, mixing evenly, then slowly adding oxalic acid, applying ultrasound with a frequency of 15-20KHz and a time of 15-20min to the dispersion after mixing evenly, leaving the mixture to stand for 30-40min, and filtering to obtain a liquid bentonite composite.
6. The anti-fading dyed fabric according to claim 1, characterized in that: The insect secretion is the lacquer liquid secreted by lacquer insects.
7. The anti-fading dyed fabric according to claim 1, characterized in that: The onion extract is obtained by crushing onions, soaking them in ethanol, and then filtering, concentrating and spray-drying the extract. The eucalyptus leaf extract is obtained by crushing the eucalyptus leaves, soaking them in ethanol, and then filtering, concentrating and spray-drying the extract. The honey locust extract is obtained by crushing mature honey locusts, soaking them in ethanol and extracting them, and then filtering, concentrating and spray-drying the extract. The Echinacea extract is obtained by crushing the mature Echinacea whole plant, soaking it in ethanol for extraction, and then filtering, concentrating and spray-drying the extract.
8. The anti-fading dyed fabric according to claim 1, characterized in that: The grey cloth is woven from polyester fibers.
9. A method for producing a fade-resistant dyed fabric according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Dispersing the colorant in deionized water, mixing evenly, respectively adding onion extract, eucalyptus leaf extract, sapodilla-echinacea complex and bentonite complex to the dispersion, mixing evenly, then adding insect secretions to the dispersion, mixing evenly, applying ultrasound at a frequency of 30-40 KHz and a time of 30-40 min to the dispersion to obtain a dye solution; S2. Control the temperature of the dye solution to 50-55°C, soak the grey cloth in the dye solution for 30-40 minutes, and stir continuously during the soaking period; S3, taking out the grey cloth and performing drying and curing treatment to obtain the anti-fading dyed fabric.